Hubungan Perceived Behavior Control Dengan Intensi Mahasiswa S1 Keperawatan Dalam Memberikan Pertolongan Bantuan Hidup Dasar Di Universitas Muhammadiyah Kalimantan Timur - Dwilana, Asindra; Astuti, Zulmah; Muflihatin, Siti Khoiroh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Cardiac arrest is a condition of sudden cessation of heart function in people who have or have not been diagnosed with heart disease before, people who have heart arrest will be fatal if not quickly treated or overcome and cardiac arrest is a condition that is required to be given immediate help. The purpose of this study is to find out whether there is a relationship between perceived behavior control and the intention of nursing s1 students in providing first aid in cardiac arrest cases. This study uses descriptive correlation with cross sectional approach. The sample in this study was 269 respondents and used total sampling techniques. Data were obtained using questionnaires and analyzed using chi-squares with significant values ≤ 0.05. The results of the study of 269 respondents based on bivariate analysis stated that PBC with Student Intentions obtained a significant value of P = 0.005 which means P < 0.05, then it can be stated that there is a Relationship between Perceived Behavior Control and Intentions of S1 Nursing Students in Providing Basic Life Support Assistance at the University of Muhammadiyah East Kalimantan. It is stated that there is a Perceived Behavior Control Relationship with the Intention of S1 Nursing Students in Providing Basic Life Support at the University of Muhammadiyah East Kalimantan.